One-stage tubularized urethroplasty using the free inner plate of the foreskin in the treatment of proximal hypospadias - Tong Shi; Yan-Kun Lin; Qiao Bao; Wei-Hua Lao; Ke-Yu Ouyang (BMC, 2022)
Abstract Objective This study summarizes the short-term efficacy of the one-stage tubularized urethroplasty using the free inner in proximal hypospadias. Methods A retrospective analysis was conducted on 42 patients with proximal hypospadias. All cases were treated with one-stage tubularized urethroplasty from January 2020 to June 2021. The postoperative complications like urethral fistula, urethral stricture, diverticulum, and split penis head were recorded. Results Patients were followed up for 3 to 15 months (an average of 8.5 months). A total of 26 cases (62%) were repaired without any complication. Five patients (11.9%) developed urinary fistulas and underwent secondary repair: three cases with anastomotic fistulas and two cases of coronal fistulas. Nine patients (21.4%) had stenosis of the head segment of the penis, six (14.3%) had stenosis that was relieved by urethral dilatation combined with topical mometasone furoate 1 month after urethral catheter removal. Two patients (4.8%) had severe stenosis with secondary surgical stenosis incision, and one (2.4%) had combined urethral diverticulum in which urethral stenosis incision and diverticulectomy were performed. Conclusions Tubularized urethroplasty using the free inner bears the advantages of easy access, reduced short-term complications, low incidence of diverticula.